2020
DOI: 10.2196/15112
|View full text |Cite
|
Sign up to set email alerts
|

A Pedometer-Guided Physical Activity Intervention for Obese Pregnant Women (the Fit MUM Study): Randomized Feasibility Study

Abstract: Background Obesity in pregnancy is a growing problem worldwide, with excessive gestational weight gain (GWG) occurring in the majority of pregnancies. This significantly increases risks to both mother and child. A major contributor to both prepregnancy obesity and excessive GWG is physical inactivity; however, past interventions targeting maternal weight gain and activity levels during the antenatal period have been ineffective in women who are already overweight. Pedometer-guided activity may offe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
(32 reference statements)
1
20
0
2
Order By: Relevance
“…Furthermore, our study and the study by Simmons et al [ 31 ] observed that women in the intervention group also spent less time sitting than women in the control group. In addition, we found that women in the intervention group increased their physical activity at T1 compared with T0, which was derived from the increase in physical activity by walking, as described by Darvall et al [ 17 ]. We observed 4 women with vigorous or high moderate physical activity, 3 (75%) of whom were derived from occupational physical activity and low walking physical activity at T0.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, our study and the study by Simmons et al [ 31 ] observed that women in the intervention group also spent less time sitting than women in the control group. In addition, we found that women in the intervention group increased their physical activity at T1 compared with T0, which was derived from the increase in physical activity by walking, as described by Darvall et al [ 17 ]. We observed 4 women with vigorous or high moderate physical activity, 3 (75%) of whom were derived from occupational physical activity and low walking physical activity at T0.…”
Section: Discussionsupporting
confidence: 64%
“…Pollak et al [ 35 ], based on n=34 (22 women in the chat group and 12 women in the SMS text messaging group) women who were pregnant and had obesity, provided health counseling for the management of GWG through SMS text messaging and a chat with professionals and observed a difference of 2.7 kg, which was similar to the GWG observed in our study. However, a recent RCT that included n=30 (10 per group for control, app, and app-coach) women who were pregnant and had obesity achieved a difference of 5.3 kg between the women who were pregnant and used a smartwatch linked to an app and the women who were pregnant and underwent an in-person coaching intervention or the group that used a smartwatch [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Über die Apps können anschließend Fortschritte angezeigt werden und im Falle eines Über-oder Unterschreitens der Normwerte von Gesundheitsparametern, wie zum Beispiel der Gewichtsentwicklung, die Interventionsintensität angepasst oder Lösungsvorschläge aufgezeigt werden. In einigen Studien wurden gesundheitsbezogene Ziele mit der sogenannten SMART Methode festgelegt [49,52,59]. SMART steht für specific, measurable, achievable und time bound.…”
Section: Digital-gestützte Lebensstilinterventionenunclassified
“…Although the application of a pedometer for the control of gestational weight gain seems controversial based on the abovementioned meta-analysis, one of the most important questions is related to the use of a pedometer by obese women, because they may be reluctant to exercise and that could be one of the reasons why they are obese. Even in a recent multiinstitutional study conducted in Australia which used a randomised controlled trial in order to assess a pedometer-based intervention to increase activity and reduce excessive weight gain in pregnant women, the conclusion of the study showed negative results with the notion that the improvement of compliance with activity data recording and behavioural interventions delivered [30]. However, there are promising reports on the use of a pedometer for the management of overweight and obese pregnant women by active intervention with individualised nutritional support and individual exercise plans.…”
Section: Pregnant Conditionmentioning
confidence: 99%